Interpretive case study to understand online communication in an e-tendering project implementation - Nurdin, Nurdin; Pettalongi, Sagaf Sulaiman (Faculty of Communication Sciences Universitas Padjadjaran, 2022)
The presence of social media has encouraged the merger of online communication between the government and the community. This phenomenon provides an opportunity for researchers to simultaneously understand the process of government communication online and offline by using an interpretive case study approach. This study aims to demonstrate the use of a qualitative interpretive case study approach to explain the effectiveness of local government communication with local business people in the online context regarding implementing the e-tendering system. This study used a qualitative interpretive method. We conducted both offline and online research to compare the consistency of the data in our study. Using the case study of government and contractors' communication in implementing e-tendering in a regency in South Sulawesi, we gathered data through face-to-face interviews and observed online communication on social media. This study's results indicate an inconsistency in government communication between the online and offline contexts regarding the perception of e-tendering issues. Our findings can be used to increase our understanding of the government's communication strategy with local business people in an online and offline context. Our study also shows that using new media in qualitative interpretive studies can reduce challenges in participant recruitment and access to research sites. However, our study faced challenges on ethical issues regarding communication material shared on social media. Future studies should focus on how ethical issues can be reduced.